New species of Neotropical Melanagromyza Hendel (Diptera: Agromyzidae) from Asteraceae flower heads - Braun, Marina Reiter; Prado, Angelo Pires Do; Lewinsohn, Thomas Michael (Zootaxa, 2009)
Agromyzids are well documented on plants of economic importance, especially those species whose larvae leave external marks on the plant, such as mines. They are far less known for non-commercial plants, particularly in tropical countries. In North American compilations of agromyzids, most of the species associated with Asteraceae flower heads belong in the genus Melanagromyza Hendel. Here we record five new seed-eating Melanagromyza species from the Brazilian Cerrado in the state of São Paulo: M. falciformis sp. nov., M. lanciformis sp. nov., M. longomembranacea sp. nov., M. multivora sp. nov. and M. vernonieaevora sp. nov.